Pharmaceutical Regulation in Central and Eastern European Countries: A Current Review - Kawalec, Paweł; Tesar, Tomas; Vostalova, Lenka; Draganic, Pero; Manova, Manoela; Savova, Alexandra; Petrova, Guenka; Rugaja, Zinta; Männik, Agnes; Sowada, Christoph; Stawowczyk, Ewa; Harsanyi, Andras; et al. (Frontiers in Pharmacology, 2017)
Objectives: The aim of this study was to review reimbursement environment as well as pricing and reimbursement requirements for drugs in selected Central and Eastern Europe (CEE) countries. Methods: A questionnaire-based survey was performed in the period from November 2016 to March 2017 among experts involved in reimbursement matters from CEE countries: Bulgaria, Croatia, Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Slovakia, and Romania. A review of requirements for reimbursement and implications of Health Technology Assessment (HTA) was performed to compare the issues in above-mentioned countries. For each specified country, data for reimbursement costs, total pharmaceutical budget, and total public health care budget in the years 2014 and 2015 were also collected. Questionnaires were distributed via emails and feedback data were obtained in the same way. Additional questions, if any, were also submitted to respondents by email. Pricing and reimbursement data were valid for March 2017. Results: The survey revealed that the relation of drug reimbursement costs to total public healthcare spending ranged from 0.12 to 0.21 in the year 2014 and 2015 (median value). It also revealed that pricing criteria for drugs, employed in the CEE countries, were quite similar. External reference pricing as well as internal reference pricing were common in mentioned countries. Positive reimbursement lists were valid in all countries of the CEE region, negative ones were rarely used; reimbursement decisions were regularly revised and updated in the majority of countries. Copayment was common and available levels of reimbursement differed within and between the countries and ranged from 20% to 100%. Risk-sharing schemes were often in use, especially in the case of innovative, expensive drugs. Generic substitution was also possible in all analyzed CEE countries, while some made it mandatory. HTA was carried out in almost all of the considered CEE countries and HTA dossier was obligatory for submitting a pricing and reimbursement application. Conclusions: Pricing and reimbursement requirements are quite similar in the CEE region although some differences were identified. HTA evaluations are commonly used in considered countries.